2018
DOI: 10.1007/s10639-018-9765-8
|View full text |Cite
|
Sign up to set email alerts
|

Survey results on adults and cybersecurity education

Abstract: Cyberattacks and identity theft are common problems nowadays where researchers often say that humans are the weakest link the security chain. Therefore, this survey focused on analyzing the interest for adults for 'cyber threat eduction seminars', e.g., how to project themselves and their loved ones. Specifically, we asked questions to understand a possible audience, willingness for paying / time commitment, or fields of interest as well as background and previous training experience. The survey was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
(3 reference statements)
1
20
0
Order By: Relevance
“…Those assets include networked devices, services, infrastructure, personnel, telecommunications systems, applications, and all of transmitted and/or stored information within the cyber environment, in order to secure the organization and users’ assets based on three main objectives consisting of availability, integrity, and confidentiality (ITU-T, 2008 ). Therefore, it can be stated that cybersecurity is a crucial factor in this era and has become a critical in this age of digital transformation (Ahmed et al, 2019 ; Ricci et al, 2019 ). It is the protection of security and privacy against cyber-attacks due to security risks and vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those assets include networked devices, services, infrastructure, personnel, telecommunications systems, applications, and all of transmitted and/or stored information within the cyber environment, in order to secure the organization and users’ assets based on three main objectives consisting of availability, integrity, and confidentiality (ITU-T, 2008 ). Therefore, it can be stated that cybersecurity is a crucial factor in this era and has become a critical in this age of digital transformation (Ahmed et al, 2019 ; Ricci et al, 2019 ). It is the protection of security and privacy against cyber-attacks due to security risks and vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This means that changing an approach can deceive users although they have basic cybersecurity skills. Ricci et al ( 2019 ) conducted a survey with 233 subjects and found that many of them were worried about cyber threats/attacks and also about their children exploring the online domain. The majority of them were interested in learning more about cybersecurity if their employers would support the costs offor cybersecurity training.…”
Section: Introductionmentioning
confidence: 99%
“…Ricci et al stated that people are generally the weakest link in the security chain in terms of cyber-attacks and identity theft Ricci et al. ( 2019 ). Cabaj et al stated that the current cyber security workforce is not sufficient to meet the growing demand for qualified cyber security professionals and the shortage will increase (Cabaj et al., 2018 ).…”
Section: Background and Related Workmentioning
confidence: 99%
“…In conclusion, the authors stressed the importance of enhancing the current cybersecurity awareness programs, with particular focus to those dedicated to the younger generations. Ricci et al [25] surveyed the interest in cyber threat education among adults. Most respondents of the survey were concerned about cybersecurity threats, and their impacts on everyday life.…”
Section: Literature Reviewmentioning
confidence: 99%